Group work as an incentive for learning – students’ experiences of group work - Hammar Chiriac, Eva (Frontiers in Psychology, 2014)
Group work is used as a means for learning at all levels in educational systems. There is strong scientific support for the benefits of having students learning and working in groups. Nevertheless, studies about what occurs in groups during group work and which factors actually influence the students’ ability to learn is still lacking. Likewise, the question of why some group work is successful and other work results in the opposite is still unsolved. The aim of this article is to add to the current level of knowledge and understandings regarding the essence behind successful group work in higher education. This research is focused on the students’ experiences of group work and learning in groups, which is an almost non-existing aspect of research on group work prior to the beginning of the 21st century. A primary aim is to give university students a voice in the matter by elucidating the students’ positive and negative points of view and how the students assess learning when working in groups. Furthermore, the students’ explanations of why some group work ends up being a positive experience resulting in successful learning, while in other cases, the result is the reverse, are of interest. Data were collected through a study-specific questionnaire, with multiple choice and open-ended questions. The questionnaires were distributed to students in different study programs at two universities in Sweden. The present result is based on a reanalysis and qualitative analysis formed a key part of the study. The results indicate that most of the students’ experiences involved group work that facilitated learning, especially in the area of academic knowledge. Three important prerequisites (learning, study-social function and organization) for group work that served as an effective pedagogy and as an incentive for learning were identified and discussed. All three abstractions facilitate or hamper students’ learning, as well as impact their experiences with group work.